2023
DOI: 10.1021/acs.molpharmaceut.3c00101
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Carbohydrate-Based Nanogel Formulation to Sensitize Hypoxic Tumors

Abstract: Solid tumors are often poorly vascularized, which impairs oxygen supply and drug delivery to the cells. This often leads to genetic and translational adaptations that promote tumor progression, invasion, metastasis, and resistance to conventional chemo-/radiotherapy and immunotherapy. A hypoxia-directed nanosensitizer formulation of a hypoxia-activated prodrug (HAP) was developed by encapsulating iodoazomycin arabinofuranoside (IAZA), a 2-nitroimidazole nucleoside-based HAP, in a functionally modified carbohyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…To inhibit the expression of the CDC20 gene, siRNA was encapsulated in nanoparticles (HRNP) consisting of self-assembled 2-nitroimidazole (NI)-modified peptides and cationic lipid compounds. Since NI can be reduced to 2-aminoimidazole (AI) under tumor cell hypoxia, it subsequently leads to the decomposition of HRNP and the rapid release of cargo (Figure A) . It was subsequently demonstrated that silencing CDC20 had an effect on the proliferation of tumor cells, and the results showed that HRNP/siCDC20 significantly inhibited cell proliferation compared with that of the untreated group and the free genome (Figure B).…”
Section: Tme-based Stimuli-responsive Rna Delivery Systemsmentioning
confidence: 96%
“…To inhibit the expression of the CDC20 gene, siRNA was encapsulated in nanoparticles (HRNP) consisting of self-assembled 2-nitroimidazole (NI)-modified peptides and cationic lipid compounds. Since NI can be reduced to 2-aminoimidazole (AI) under tumor cell hypoxia, it subsequently leads to the decomposition of HRNP and the rapid release of cargo (Figure A) . It was subsequently demonstrated that silencing CDC20 had an effect on the proliferation of tumor cells, and the results showed that HRNP/siCDC20 significantly inhibited cell proliferation compared with that of the untreated group and the free genome (Figure B).…”
Section: Tme-based Stimuli-responsive Rna Delivery Systemsmentioning
confidence: 96%
“…The optimization of nanogels mentioned above was conducted by Diaz-Dussan in a recently published paper [ 58 ]. The study focuses on the development of a hypoxia-directed nanosensitizer formulation for the treatment of solid tumors.…”
Section: Galactose For Theranosticsmentioning
confidence: 99%
“…These glycopolymers are known for their ease of preparation and low cytotoxicity. These glycopolymers were found to be promising in drug/gene delivery, surface coatings, hydrogels and tissue engineering [ 28 , 32 , 52 , 53 , 54 , 55 ]. A hydrophilic polymer with sugar moieties was designed and prepared as the hydrogel precursor.…”
Section: Introductionmentioning
confidence: 99%